The combination of ibrutinib and rituximab demonstrates activity in first‐line follicular lymphoma. (16th March 2020) - Fowler, Nathan H.; Nastoupil, Loretta; De Vos, Sven; Knapp, Mark; Flinn, Ian W.; Chen, Robert; Advani, Ranjana H.; Bhatia, Sumeet; Martin, Peter; Mena, Raul; Davis, Richard Eric; Neelapu, Sattva S.; et al.
Summary: This phase 2 study evaluated the activity and safety of ibrutinib, a Bruton's tyrosine kinase inhibitor, plus rituximab in adults with previously untreated follicular lymphoma. Patients received once‐daily ibrutinib 560 mg continuously plus once‐weekly rituximab 375 mg/m 2 for 4 weeks beginning Week 1 (Arm 1, n  = 60) or Week 9 (following an 8‐week ibrutinib lead‐in) to explore biomarkers (Arm 2, n  = 20). The primary endpoint was the best overall response rate (ORR). The median age was 58 years; most had an Eastern Cooperative Oncology Group Performance Status of 0 (74%) and Stage III/IV disease (84%). At a median study follow‐up of 34 months in Arm 1 and 29 months in Arm 2, ORRs were 85% [95% confidence interval (CI) 73–93] and 75% (95% CI 51–91), respectively, with complete responses in 40% and 50%. The median duration of response was not reached in either arm; 30‐month progression‐free and overall survival rates were 67% and 97% (Arm 1) and 65% and 100% (Arm 2). The most common adverse events were fatigue, diarrhoea and nausea. Higher grade (Grade 3/4) haematological, haemorrhagic and cardiac events occurred infrequently. Ibrutinib plus rituximab was active and tolerable in first‐line follicular lymphoma.